2020
DOI: 10.1024/0301-1526/a000872
|View full text |Cite
|
Sign up to set email alerts
|

Large vessel vasculitis secondary to granulocyte-colony stimulating factor

Abstract: Summary: Aortitis is a rare entity that may cause fever of unknown origin. This entity has a wide various etiologies, which main cause is rheumatologic, but not only. Iatrogenia has also been described, including chemotherapy and supporting treatment (like granulocyte-colony stimulating factor in oncological patients. The evidence in favour of this pharmacological link is growing. The differential diagnosis of fever, in febrile neutropenia setting, can be difficult to itemize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In one case of large-vessel vasculitis after pegfilgrastim administration, the patient was transitioned to nonpegylated G-CSF with additional cycles of chemotherapy administered without relapse of vasculitis [ 16 ]. Still, other case reports indicate that both pegylated and nonpegylated G-CSF can be associated with the development of aortitis [ 10 ]. One case report suggested that those who received pegylated G-CSF required steroids and those who received nonpegylated G-CSF had resolution of vasculitis without steroids [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one case of large-vessel vasculitis after pegfilgrastim administration, the patient was transitioned to nonpegylated G-CSF with additional cycles of chemotherapy administered without relapse of vasculitis [ 16 ]. Still, other case reports indicate that both pegylated and nonpegylated G-CSF can be associated with the development of aortitis [ 10 ]. One case report suggested that those who received pegylated G-CSF required steroids and those who received nonpegylated G-CSF had resolution of vasculitis without steroids [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some patients with G-CSF-vasculitis improved with discontinuation of G-CSF alone and without corticosteroid therapy [ 2 , 4 ], aortic dissection and aneurysm have been reported as rare complications, which can appear in an acute course within a few weeks after the onset of vasculitis [ 7 , 8 ]. The cases treated with corticosteroids reached fever resolution within a few days [ 9 - 15 ], while it took one to three weeks for those treated without corticosteroids to reach fever resolution [ 1 , 4 , 13 , 16 - 20 ]. Since G-CSF-induced vasculitis occurs mainly in patients with malignancy, persistent fever due to G-CSF-induced vasculitis leads to the postponement of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%